Pengaruh Edukasi Tentang Pemeriksaan Payudara Sendiri (SADARI) Melalui Media Leaflet terhadap Pengetahuan dan Sikap Remaja Putri - Adrisyahrani, Shalma Putri; Sugita, Sugita; Andriyani, Asti; Mulati, Triwik Sri (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Early detection of breast cancer can be carried out through Breast Self-Examination (BSE), which helps identify any lumps or abnormalities in the breast. However, a lack of awareness about BSE among adolescents affects their ability to perform it correctly. Educating young women about BSE through leaflet media can significantly enhance their knowledge and attitudes toward it. This activity aims to provide SADARI education based on leaflets to young women in Polonharjo Village and to monitor changes in knowledge and attitudes through pre- and post-session assessments. Methods The SADARI education programme based on leaflets (±20 minutes) was given to 75 adolescent girls, with measurements of knowledge (structured questionnaire) and attitude (Likert scale) before and after the session. Data were summarised descriptively and analysed in pairs. Results: The results revealed a significant increase in the average knowledge score, which rose from 13.92 to 21.53 after the intervention. Similarly, the average attitude score increased from 43.61 to 62.63. The test indicated a significant improvement in knowledge post-intervention. Conclusion: Providing education about Breast Self-Examination (BSE) through leaflet media effectively enhances the knowledge and attitudes of young women in X Village regarding breast health.